2019
DOI: 10.3233/nre-182637
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postural deformities on back function and pain in patients with Parkinson’s disease

Abstract: BACKGROUND: Postural deformities, such as Pisa syndrome (PS), and camptocormia and antecollis (C&A) are common in patient with Parkinson's disease (PwPD). These deformities can lead to back disability and pain with different mechanisms, including abnormal loading or stress on soft tissues as muscles, lumbar discs and ligaments. OBJECTIVES: To evaluate the effect of different postural deformities including PS and C&A on back function and pain in PwPD. METHODS: The function, disability and pain were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…ROC curves showed that patients with LTB of 10.5°might have moderate/severe motor impairment 16 . Another two studies demonstrated that camptocormia, antecollis, and Pisa syndrome were associated with severe impairment of neck and back functions, as well as pain in PD patients 41,42 . In our study, weak to moderate correlations were identified between IPA with common PD clinical scales, which indicates that IPA can reflect the clinical severity of postural abnormalities in PD to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…ROC curves showed that patients with LTB of 10.5°might have moderate/severe motor impairment 16 . Another two studies demonstrated that camptocormia, antecollis, and Pisa syndrome were associated with severe impairment of neck and back functions, as well as pain in PD patients 41,42 . In our study, weak to moderate correlations were identified between IPA with common PD clinical scales, which indicates that IPA can reflect the clinical severity of postural abnormalities in PD to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Among the postural changes, a forward-stooped posture with flexion of the cervical and thoracic spine is common. 1 , 2 Forward stooped posture can cause significant discomfort, 3 contributes to an increased risk of falls 4 , 5 and reduces the quality of life. 3 , 6 10 Treatment options are limited as postural changes (like other axial symptoms such as postural instability and gait disorders) do not respond well to pharmacological therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Forward stooped posture can cause significant discomfort, 3 contributes to an increased risk of falls 4 , 5 and reduces the quality of life. 3 , 6 10 Treatment options are limited as postural changes (like other axial symptoms such as postural instability and gait disorders) do not respond well to pharmacological therapy. 1 , 6 , 11 13 Deep brain stimulation appears to have some efficacy in stooped posture in small studies, 14 , 15 but the lack of randomized controlled trials of deep brain stimulation for stooped posture, strict selection criteria, its invasive nature, and its limited availability at specialized centres limit its use for the general patient population.…”
Section: Introductionmentioning
confidence: 99%
“…With population aging, the number of patients with this age-related disorder is increasing [1]. In severe cases, PD causes postural disorder, such as anterocollis, Pisa syndrome, and camptocormia [2][3][4][5]. Reports have shown that these postural abnormalities increase susceptibility to rigid spinal deformities [2,3] and that patients with PD develop adult spinal deformity (ASD) more frequently than the general population in the same age groups [6].…”
Section: Introductionmentioning
confidence: 99%